2013
DOI: 10.5536/kjps.2013.40.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an H5N3 Influenza Virus Isolated from Spot-Billed Duck

Abstract: Among the 16 hemagglutinin (HA) subtypes of avian influenza virus (AIV), only the H5 and H7 subtypes have caused highly pathogenic avian influenza (HPAI) in poultry. However, most H5 or H7 subtype viruses are categorized as low pathogenic avian influenza (LPAI). Some AIVs, including the H5 and H7 HPAI viruses, have shown the ability to infect humans directly. In this study, we describe the biological and molecular characterization of an H5N3 AIV (SBD/KR/KNU SYG06/06) isolated from spot-billed duck (Anas poecil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Molecular characterization identified the pathogenic potential of the KNU18-91 isolate and showed that it had a PQRETR/ GLF sequence at the HA cleavage site, suggesting low pathogenicity [8]. Similar to that reported by Lee et al [22] (2013) for H5N3 isolates in South Korea, the fragment deletion in the NA gene stalk region that represents wild bird virus adaptation to a new host was absent in the isolate under study, supporting LPAI of the new isolates [22,74]. The 274H and 292R residues retained viral sensitivity to neuraminidase (oseltamivir and zanamivir) inhibitors [75].…”
Section: Discussionsupporting
confidence: 81%
“…Molecular characterization identified the pathogenic potential of the KNU18-91 isolate and showed that it had a PQRETR/ GLF sequence at the HA cleavage site, suggesting low pathogenicity [8]. Similar to that reported by Lee et al [22] (2013) for H5N3 isolates in South Korea, the fragment deletion in the NA gene stalk region that represents wild bird virus adaptation to a new host was absent in the isolate under study, supporting LPAI of the new isolates [22,74]. The 274H and 292R residues retained viral sensitivity to neuraminidase (oseltamivir and zanamivir) inhibitors [75].…”
Section: Discussionsupporting
confidence: 81%
“…Lee et al., 2011; J.‐H. Lee et al., 2013). Both migratory populations from northern Russia, China and Mongolia and resident populations usually move to river estuaries and form huge wintering flocks from October to March (W.‐S.…”
Section: Methodsmentioning
confidence: 99%
“…The mandarin, mallard and spot-billed duck, well-known winter migrants and resident birds in South Korea, were selected since most HPAI viruses have been detected in them (E.-T. H.-R. Kim et al, 2011;D.-H. Lee et al, 2011;J.-H. Lee et al, 2013). Both migratory populations from northern Russia, China and Mongolia and resident populations usually move to river estuaries and form huge wintering flocks from October to March (W.-S. Shin et al, 2012).…”
Section: Study Species and Occurrence Datamentioning
confidence: 99%
See 2 more Smart Citations